SIMULATION PROGRAM SKILLS FOR CHEMICAL ENGINEERING GRADUATES - Nuraini, Annisaa; Setyowati, Dias Afifah; Kurniyanto, Valentinus Enrico; Fitriah, Fitriah; Ni'mah, Kamilah Pathun; Aliffiantika, Nindya; Pusvitasari, Anggun Bunga; Sari, Dessy Agustina (JURNAL PENDIDIKAN GLASSER, 2024)
A bachelor's degree in chemical engineering enhances one's capacity to adapt both hard and soft skills in the classroom and at work to the quick changes in technology and increasing competitiveness in the professional world. This motivates an individual who has graduated from chemical engineering to enhance the caliber of their work. Technology for simulation programming is one of the hard skills he needs to possess. In the realm of chemical engineering, these abilities encompass not only using Microsoft Office but also making objects work with other software. Through theoretical research on cases in the process industry, the simulation program is used. Prioritizing the operational foundation of an application is essential for work in the chemical sector. It is recommended that a graduate of chemical engineering possess software capabilities in order to facilitate their employment in the workforce. Basic requirements and increased proficiency can be supported by theoretical and data processing techniques. This article discusses the need for software skills in the field of chemical engineering, such as Aspen HYSYS, Matlab, AutoCAD P&ID, and Scilab, using a literature study methodology. This endeavor is a method of looking through library data for pertinent articles and then delving deeper into an article's content. The purpose of this article review is to balance hard and soft skills in order to determine how software is used in the field of chemical engineering and what is required in the chemical industry.